2011
DOI: 10.3346/jkms.2011.26.3.454
|View full text |Cite
|
Sign up to set email alerts
|

Low Level Light Could Work on Skin Inflammatory Disease: A Case Report on Refractory Acrodermatitis Continua

Abstract: Low level laser or light treatment on the various clinical condition is getting considerable attention now. However, there has been no report about the clinical effect of low level polarized polychromatic noncoherent light (LPPL) on the inflammatory skin disease. We experienced a case of acrodermatitis continua in a pregnant woman refractory to any conventional treatment including the most potent topical steroid. She was successfully treated with LPPL. LPPL could be a possible treatment modality producing subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…In a study of using polarized light in the treatment of acrodermatitis continua, 4 times the clinical exposure of LPPL with topical steroid application displayed clinical advance and the impact was maintained for several months without demand for further topical steroid utilization. It was assumed in this study that polarized light could act favorably on the inflammatory skin conditions without any side effects [9]. Eventually, BLT may help to treat skin ailments such as atopic dermatitis through relieving pain as well as inflammation, via promoting a healing response in the skin [25].…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…In a study of using polarized light in the treatment of acrodermatitis continua, 4 times the clinical exposure of LPPL with topical steroid application displayed clinical advance and the impact was maintained for several months without demand for further topical steroid utilization. It was assumed in this study that polarized light could act favorably on the inflammatory skin conditions without any side effects [9]. Eventually, BLT may help to treat skin ailments such as atopic dermatitis through relieving pain as well as inflammation, via promoting a healing response in the skin [25].…”
Section: Methodsmentioning
confidence: 95%
“…The Bioptron Light Therapy (BLT) is a common restricted light treatment method with an emitting light that is related to the element of the electromagnetic waves generated directly by the sun without serious UV radiation. BLT devices emit light including a span of wavelengths that match the visible light in addition to infrared radiation, both of which have been stated to animate the physiological response [9]. Furthermore, BLT can improve skin healing and lessen the embarrassment correlated with different skin dysfunctions.…”
mentioning
confidence: 99%
“…It is reported that a linear polarized beam (coherent or non-coherent) in the VIS-IR range with an oscillating electric field E can cause biological effects in cells through electrons oscillation inducement [16][17][18][19]. The underlying mechanism has been described in terms of photobiomodulation [26]. Photobiomodulation changes natural biochemical responses of the cell within the normal range of its function.…”
Section: Theorymentioning
confidence: 99%
“…The photobiomodulation may affect the cellular milieu in various disease conditions and promote spontaneous healing [26,27]. It is reported that illuminating microorganism with appropriate wavelengths can enhance Adenosine Triphosphate (ATP) synthesis by altering the mitochondrial membrane potential [16][17][18]26,27]. In addition, in photoexcited ATP, the charge distribution of the phosphate structure is changed, possibly causing a rapid reaction with other substrates.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation